If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f = 4f + 10 Reorder the terms: 3f = 10 + 4f Solving 3f = 10 + 4f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4f' to each side of the equation. 3f + -4f = 10 + 4f + -4f Combine like terms: 3f + -4f = -1f -1f = 10 + 4f + -4f Combine like terms: 4f + -4f = 0 -1f = 10 + 0 -1f = 10 Divide each side by '-1'. f = -10 Simplifying f = -10
| X-1+5x-3+5x-3= | | 6+6r=18 | | 9+9m=-9+6m+5m | | -16=30x+15x^2 | | 6x-15x=18 | | -2x-39=-6x+29 | | 6a+4a-3a= | | 63x^8=0 | | 4k+ar=r-7y | | -3(t-5)+5t=7t-4 | | X^2+6x-1=7x-9 | | -4.19+11.5c=10c-0.87+1.7c | | 6x+3x-6=10x+5 | | -8-5v=-9v | | -4y+8z=32 | | -5-8a=-45 | | X+6=5(2x-2) | | y(x^2+y^2)dx=x^3dy | | -2-10w=4-8w | | r=9.6 | | 14+12w=16+9w | | -11(4+k)=220 | | 15x(-2-x)-12=4 | | (3.14)x^2=28.26 | | 3q-2=7 | | -8m=4 | | 6r+10=124 | | -2b+6-4=18 | | -6u=10-5u | | 5.9s=3(-3.4s-15.91) | | 5x+6=16x+-3x+54 | | x-10=104 |